2020
DOI: 10.3390/ijms21197138
|View full text |Cite
|
Sign up to set email alerts
|

Weak Ultraviolet B Enhances the Mislocalization of Claudin-1 Mediated by Nitric Oxide and Peroxynitrite Production in Human Keratinocyte-Derived HaCaT Cells

Abstract: A tight junction (TJ) makes a physical barrier in the epidermal cells of skin. Ultraviolet (UV) light may disrupt the TJ barrier, but the mechanism has not been well clarified. Weak UVB (5 mJ/cm2) caused mislocalization of claudin-1 (CLDN1), a component of the TJ strand, and disruption of TJ barrier in human keratinocyte-derived HaCaT cells. The UVB-induced mislocalization of CLDN1 was inhibited by monodansylcadaverine (MDC), a clathrin-dependent endocytosis inhibitor, suggesting that UVB enhances the internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Once the weak UVB irradiated the cells, the generation of reactive nitrogen species (RNS) was stimulated, which induced mislocalization of CLND1 [ 5 ]. Next, the effects on RNS generation were investigated using specific probes for Ca 2+ influx, nitrogen oxide (NO) production, and peroxynitrite production, which is a more reactive form of RNS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the weak UVB irradiated the cells, the generation of reactive nitrogen species (RNS) was stimulated, which induced mislocalization of CLND1 [ 5 ]. Next, the effects on RNS generation were investigated using specific probes for Ca 2+ influx, nitrogen oxide (NO) production, and peroxynitrite production, which is a more reactive form of RNS.…”
Section: Resultsmentioning
confidence: 99%
“…A severe level of ultraviolet ray-B (UVB) irradiation causes reactive oxygen species (ROS), reactive nitrogen species (RNS), and DNA damage, resulting in the dysfunction of the skin barrier and an elevation of risk factors for skin cancer [ 6 ]. In contrast, non-cytotoxic “weak” UVB irradiation stimulates RNS generation, but not ROS, leading to barrier dysfunction associated with the mislocalization of CLDN1 in our previous report [ 5 ]. Since our skin is constantly exposed to sunlight throughout our lives, an effective protection strategy is needed to maintain skin health against weak UVB.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Overexpression of CADM1 shows an increased Claudin-1 expression, while the silencing CADM1 improves the intestinal barrier function. Claudin-1 is responsible for barrier function in the skin [ 76 , 77 ], therefore CADM1 in keratinocytes is expected to exhibit a positive regulation in the skin barrier and have a beneficial impact on skin barrier-related diseases [ 78 ]. However, the actual impact of CADM1 in epidermal barrier function remains unclear.…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%
“…More importantly, treatment with recombinant TNC polypeptide increased collagen expression by activating the transforming growth factor- β (TGF-β) signaling pathway. Kobayashi et al [ 12 ] showed that UVB enhances the mis-localization of claudin-1 through NO and peroxynitrite production in a human keratinocyte cell line, which can explain the weakening of skin barrier and the deterioration of skin condition upon exposure to UVB. Lee et al [ 13 ] discovered that a synthetic retinoid, seletinoid G, is effective in improving skin barrier function, which they purported to be due to its wound-healing effects.…”
mentioning
confidence: 99%